Desenvolvimento de um sistema para dimensionamento, análise e otimização de circuitos de preparação de minérios - Henrique Goncalves Teixeira (2013)
Before an execution of a mineral plant design, several simulations are realized to predict and minimize some errors. There are computational resources that help with these predictions, however these software are complex, expensive and they don´t have the objective to design a mineral equipment. The input variables of these software isnt consistent with the data used in industrial practice. Noticing the difficulties on mineral plant, the present work aims an elaboration of a software, called CIC (Comminution Integrated Circuit), to design equipment used on mineral processing plant, as jaw crushers, gyratory crushers, screens, rod mill, ball mill and hyrdocyclones. The CIC has a intuitive interface to facilitate the operation, avoiding the necessity of courses to understand it. The parameters used by CIC are from industrial practical knowledge. After data input, the user will get the necessary specifications for a mechanical engineer design and develop such equipment. The software also contains the simulation of design equipment products. Such information may be used by a mineral professional to compare the equipment available in the market, checking if the dimensions given by the manufacturers are consistent with the project. The principle of the CIC and the models used by it are stated on this work.